일 소음작업장 근로자들의 소음에 대한 인식 및 태도, 예방행위에 관한 연구 - 권수자(Su Ja Kwon); 김은희(Eun Hee Kim); 김태경(Tae Kyung Kim); 정희영(Hee Young Jung) (지역사회간호학회지, 2005)
This study was to investigate knowledge, attitude and the preventive behaviour of noise of workers exposed to harmful noise and to provide primary data for noise-exposed workers' hearing conservation and the prevention of noise induced hearing loss. Method: The subjects were 104 workers who participated voluntarily in the questionnaire. The instrument used in this study was knowledge, attitude and practice on noise-induced hearing loss tool by Rhee & Yi (1996). The data were collected from August to September, 2002 with a self-administered questionnaire. Data were analyzed by SPSS 10.0 win program for finding frequency, percentage, mean, standard deviation, t-test, and ANOVA. Results: The average age of workers was 35.9 and the current average year of working at the noise place was $5{\sim}$10 years. In the group of previous noise-exposed workers, they showed significant difference in preventive behaviors (t=4.087, p=.048). In the group of current noise-exposed workers, they showed significant difference in recognition and attitude of noise(F=4.707, p=.004). Also, the duration of wearing ear protection equipment(t=2.383, p=.019), the feeling of wearing ear protection equipment(F=3.602, p=.031) and comfortable sense of wearing ear protection (F=3.919, p=.023) was significant in the preventive behaviour of noise. Conclusion: Considering the results above, we can recognize that there are close relations among the knowledge, attitude and the preventive behaviour of noise. Therefore, it is necessary to develop education - programs for noise-exposed workers' better understanding of noise and preventive behaviors